FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OPTIMALISASI PELAKSANAAN PERAWATAN METODE KANGGURU PADA BAYI BERAT LAHIR RENDAH DI RSUD Dr. M.M. DUNDA LIMBOTO - Ani Retni; Fahmi A. Lihu (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The objective of this research is to find out the factors that correlated twith optimizing the implementation of kangaroo treatment method on newbron infants at RSUD Dr. M.M. Dunda Limboto. This research design used survey analyticalwith cross sectional study design. The samples are used 32 mothers.Collection data used questionnaires and observation froom. The data analyzed usedChi squarestatistic test. The result showed thereare correlation of knowledge level (p value 0,010), attitude (p value 0,000) and nurse’s support (p value 0,011) with optimizingimplementation of kangaroo treatment method in newborns infants at RSUD Dr. M.M. Dunda Limboto. Suggested to the hospital especially to the nurses as the service profider, Expected to develop the right program and sustainable for mothers in increasing the implementation of newbrons treatment.at home.